Judicialização da política de saúde e a pandemia da Covid-19: uma análise da atuação do Supremo Tribunal Federal em sede de controle concentrado de constitucionalidade em face dos atos do Poder Executivo e Legislativo no ano de 2020 - MIRANDA, Sara Barros Pereira de (2021)
With the beginning of the COVID-19 pandemic in Brazil, the Government was called to act in order to comply with the constitutional duty to guarantee the health of the population. Nevertheless, such action resulted in a series of conflicts that ended up being judicialized in the Federal Supreme Court, which, throughout 2020, played the role of mediator between different entities and public agencies. Therefore, this research aimed to analyze the content of the STF decisions issued in 2020 on the role of the Federal Executive and Legislative Powers in public health policies to fight the COVID-19 pandemic. As a methodological procedure, Lawrence Bardin's content analysis was used, in order to be able to understand the explicit meanings or not apparent contained in the content of the court decisions targeted by the research. Finally, it was concluded that the STF acted to resolve the political, federative and health conflicts proposed to it, in line with the dictates of the 1988 Constitution itself, whose constitutional architecture points to an increasingly greater judicialization of politics.